2016
DOI: 10.1007/s00018-016-2226-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling head and neck cancer stem cell-mediated tumorigenesis

Abstract: A large body of literature has emerged supporting the importance of cancer stem cells (CSCs) in the pathogenesis of head and neck cancers. CSCs are a sub-population of cells within a tumor that share the properties of self-renewal and multipotency with stem cells from normal tissue. Their functional relevance to the pathobiology of cancer arises from the unique properties of tumorigenicity, chemotherapy resistance, and their ability to metastasize and invade distant tissues. Several molecular profiles have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 131 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…Cancer stem cells are considered the origin of cancer cells, which are closely associated with therapeutic resistance and cancer recurrence [4,5]. Our previous study showed that CD133+CD44+ cancer stem cells isolated from the LSCC cell lines Hep2 and TU-177 by magnetic-activated cell sorting (MACS) exhibited enhanced cell viability, migration and invasive capability, colony-formation ability, and resistance to chemotherapy and irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer stem cells are considered the origin of cancer cells, which are closely associated with therapeutic resistance and cancer recurrence [4,5]. Our previous study showed that CD133+CD44+ cancer stem cells isolated from the LSCC cell lines Hep2 and TU-177 by magnetic-activated cell sorting (MACS) exhibited enhanced cell viability, migration and invasive capability, colony-formation ability, and resistance to chemotherapy and irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…For HNSCC in particular, HPV infection and multimodality therapy has to be taken into account in addition to other microenvironmental factors. Furthermore, in silico models simulated the direct and indirect interactions between HNSCC cells and endothelial cells via the VEGF-Bcl-2-CXCL8 pathway influencing vascular growth and therapy response [106,107,108,109].…”
Section: Hnscc Hierarchy Heterogeneity and Plasticitymentioning
confidence: 99%
“…Treatment decisions for HNSCC are complex, and according to the US guidelines, a multidisciplinary approach is recommended (2). However, the prognosis of HNSCC remains very poor.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) refers to a group of biologically similar cancers arising from the mucous squamous epithelia in the head and neck area. HNSCC is an aggressive cancer with poor overall survival (1)(2)(3)(4). In spite of the recent advancements in treatment modalities for HNSCC, the long-term survival rates have not significantly improved over the past decade (5).…”
Section: Introductionmentioning
confidence: 99%